2019
DOI: 10.3389/fimmu.2019.02819
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Natural Killer Cell-Derived Exosomal miR-3607-3p Inhibits Pancreatic Cancer Progression by Targeting IL-26

Abstract: Increasing evidences have suggested that natural killer (NK) cells in the tumor microenvironment are involved in the regulation of cancer development. However, the potential biological roles and regulatory mechanisms of NK cells in pancreatic cancer (PC) remain unclear. Co-culture system of NK cells with PC cells is used to test the ability of cancer cell proliferation, migration and invasion both in vitro and in vivo. And tail vein intravenous transfer was used to test metastasis in vivo. Meanwhile, extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
77
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 29 publications
(31 reference statements)
0
77
0
2
Order By: Relevance
“…NK‐EVs are also shown to deliver regulatory miRNAs to cancer cells, which could be an alternative tumour‐targeting mechanism of NK‐EVs. NK‐EVs have in two independent studies been shown to contain miR‐186 28 or miR‐3607‐3p 30 . Both miR‐3607‐3p and miR186 act as tumour suppressors, and downregulation of either in cancer tissues predicts poor patient prognosis 31,32 .…”
Section: Anti‐cancer Activity Of Nk‐evsmentioning
confidence: 99%
See 1 more Smart Citation
“…NK‐EVs are also shown to deliver regulatory miRNAs to cancer cells, which could be an alternative tumour‐targeting mechanism of NK‐EVs. NK‐EVs have in two independent studies been shown to contain miR‐186 28 or miR‐3607‐3p 30 . Both miR‐3607‐3p and miR186 act as tumour suppressors, and downregulation of either in cancer tissues predicts poor patient prognosis 31,32 .…”
Section: Anti‐cancer Activity Of Nk‐evsmentioning
confidence: 99%
“…Both miR‐3607‐3p and miR186 act as tumour suppressors, and downregulation of either in cancer tissues predicts poor patient prognosis 31,32 . In vitro, NK‐EVs were able to transfer their miR‐3607‐3p cargo to pancreatic cancer cells, but functional effects of this interaction was not investigated 30 . In another study, NK‐EVs delivered miR‐186 to neuroblastoma cell lines (LAN‐5 and CHLA‐136) upon overnight co‐culture and exerted cytotoxicity in a miR‐186‐dependent manner 28 .…”
Section: Anti‐cancer Activity Of Nk‐evsmentioning
confidence: 99%
“…In addition, NK cell-derived EVs have been shown to shuttle certain miRNAs that induce an anti-tumor response even in immunosuppressive TMEs [ 98 ], where they can exert cytotoxic effects specifically against tumor cells [ 32 ]. Indeed, the newly studied miR-3607-3p is found to be enriched in the EVs of NK cells as a way to deliver them to pancreatic cancer cells [ 99 ]. NK cell- and EV-derived miR-3607-3p inhibited the proliferation, migration and invasion of pancreatic cancer cells through the inhibition of IL-26 [ 99 ].…”
Section: Ev-mediated Crosstalk In Immune–tumor Cell Interactionsmentioning
confidence: 99%
“…Indeed, the newly studied miR-3607-3p is found to be enriched in the EVs of NK cells as a way to deliver them to pancreatic cancer cells [ 99 ]. NK cell- and EV-derived miR-3607-3p inhibited the proliferation, migration and invasion of pancreatic cancer cells through the inhibition of IL-26 [ 99 ]. These findings are consistent with the suppressive role of miR-3607-3p that has been reported in non-small cell lung cancer (NSCLC), where it has been shown to induce cell cycle arrest and inhibit tumor growth and metastasis [ 100 ].…”
Section: Ev-mediated Crosstalk In Immune–tumor Cell Interactionsmentioning
confidence: 99%
See 1 more Smart Citation